2018
DOI: 10.1016/j.cemconres.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the particle size and dosage of LDHs and concrete resistance against chloride ingress

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(30 citation statements)
references
References 50 publications
2
23
1
Order By: Relevance
“…In the above-mentioned studies, the intercalated anions were nitrite (corrosion inhibitor), nitrate, carbonate, and chloride. The most commonly studied LDH is by far MgAl-LDH [20][21][22]24,27,32,35,[37][38][39][41][42][43][44][45][46][47]49,50], followed by CaAl [16][17][18]26,[32][33][34]40], hydrotalcite [23,29,36], and modified hydrotalcite [25,28,31]. ZnAl-LDH is a new composition that has been studied in only two papers [51,52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the above-mentioned studies, the intercalated anions were nitrite (corrosion inhibitor), nitrate, carbonate, and chloride. The most commonly studied LDH is by far MgAl-LDH [20][21][22]24,27,32,35,[37][38][39][41][42][43][44][45][46][47]49,50], followed by CaAl [16][17][18]26,[32][33][34]40], hydrotalcite [23,29,36], and modified hydrotalcite [25,28,31]. ZnAl-LDH is a new composition that has been studied in only two papers [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…The use of LDH to control the cement hydration kinetics has been studied by several groups [18][19][20][21]. However, most of the work with LDH in concrete is dedicated to the mitigation of steel rebars corrosion, either in chloride media [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] or carbonated concrete [32,[41][42][43][44][45][46][47][48]. Many studies have been done in simulated concrete pore solution [35,38,43,46], just a few in mortar [31,43] and only one in concrete [16].…”
mentioning
confidence: 99%
“…Depending on the type of LDH in use, it can have a positive effect on the mechanical properties of concrete especially its compressive strength, see Table 1. LDHs have hexagonal platelet like structures and if they are able to retain their structure in mature concrete, the resulting concrete can also show enhanced flexural strength as these thin LDH platelets can act as micro-beam elements [97] between cementitious materials and therefore help in an efficient transfer of bending stresses. Table 1 presents a compilation of compressive and flexural strength enhancement of concrete together with type of LDH and dosages used by different authors.…”
Section: Effect On Mechanical Propertiesmentioning
confidence: 99%
“…From Table 1, it can be observed that Ca based LDH has a profound positive effect on mechanical properties whereas multiple entries report a Mg based LDH to have a negative or inconclusive effect on mechanical properties. Qu et al [97] used Ca based LDH and observed a strong increase in the compressive strength and flexural strength in samples with LDHs as compared with reference samples. A 17.2% increase in compressive strength was observed in samples with 1% dosage of LDH (mean particle size 3.2 µm) but only 1.7% strength increase for 2% LDH, see Figure 4.…”
Section: Effect On Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation